Automatic search algorithm for differential characteristics in ARX ciphers - Zheng-bin LIU (网络与信息安全学报)
How to compute the differential of modular addition efficiently is critical to automatic search for differential characteristic in ARX ciphers.To solve this problem,firstly,the concept of collerated difference distribution table (CDDT) was proposed.By looking up the CDDT,it was very efficient to compute the differential probability of modular addition.Secondly,extending Matsui’s algorithm to ARX cihpers and using CDDT,an automatic search algorithm was proposed,and the algorithm could give the differential characteristic with highest probability in ARX ciphers.Finally,the proposed algorithm was applied to the ARX cipher SPECK,and got the best differential characteristics for SPECK32,SPECK48 and SPECK64.